If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 39 = -2x + 7 Reorder the terms: 39 = 7 + -2x Solving 39 = 7 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 39 + 2x = 7 + -2x + 2x Combine like terms: -2x + 2x = 0 39 + 2x = 7 + 0 39 + 2x = 7 Add '-39' to each side of the equation. 39 + -39 + 2x = 7 + -39 Combine like terms: 39 + -39 = 0 0 + 2x = 7 + -39 2x = 7 + -39 Combine like terms: 7 + -39 = -32 2x = -32 Divide each side by '2'. x = -16 Simplifying x = -16
| 12.6=-49k+4(8.5k-0.6) | | 10a-9=-79 | | 3(7r-6)-9r=12r+1 | | 5x-7.5=0 | | 66=-5x+10 | | 7x-9=4(3x-1) | | X^2-18=90 | | 10-4(3x+2y)= | | -5x-20-7x=-68 | | -3(5y+6)-3(y-8)= | | -14=-8+2w | | 3(3r+3)-2(r-1)= | | 7b=4(b+30) | | 2ln(2x)=6 | | -2(3y-1)-2(y-6)= | | (x^2-2x+4)(x^2+3x-11)=0 | | x-13=19+3x | | 4(g+8)=7+4g | | 2(8q-5)=4q | | (m^2+m-6)/(m+4) | | 29-10= | | 3c+1=c+1 | | 2k-3(2k-3)=45 | | 5=7w+8w+2 | | 60=-12r | | -9(b-4)-1= | | X=842-13 | | k/17=-7/17 | | (3x+14)/5=8-2x | | 4x+2+3x-8=8 | | a-19=-25 | | 2x-y+150=180 |